Home broadband and student engagement during COVID-19 emergency remote teaching. Issue 4 (2nd October 2021) - Mac Domhnaill, Ciarán; Mohan, Gretta; McCoy, Selina
ABSTRACT: During the academic year 2019–2020, school buildings worldwide closed in response to the COVID-19 pandemic, necessitating a rapid shift to distance education. This study assessed the influence of high-speed broadband availability on student engagement with distance learning during this period in Ireland. Employing data from a representative sample of 206 secondary schools, student engagement as perceived by school principals was estimated to have been more adversely affected among schools located in areas with lower coverage of high-speed broadband. This may be partly explained by a lower probability of poorer student engagement among schools that deployed live online video teaching. While the costs and benefits must be considered, these findings may support the case for government intervention to provide greater equity in access to high-speed broadband. Where distance learning is required in future, secondary teachers should be supported in the use of live online teaching to better foster student engagement.